Relations between the State and Business in the Conditions of the “Developmental State” - A. I. Kugai; M. A. Pakhomova (Евразийская интеграция: экономика, право, политика, 2024)
Aim. To identify the mechanism of state regulation of private enterprise initiative operating in the “developmental states” of East and Southeast Asia, which ensures consistently high rates of economic growth and an increase in public welfare.Tasks. Based on a comparative analysis, to determine the characteristic features of the model of relations between the state and business in the “developmental states”, to reveal its strengths and weaknesses, the role of the ruling elite in its functioning.Methods. The central concept is the “developmental state”, the elements of which are revealed by Zia Onish, the concepts of “planned-rational state” (C. Johnson), “built-in autonomy” (P. Evans), “neopatrimonial state”, “cohesive capitalist state” and “fragmented multi-class state” (A. Koli). The model of the relationship between the state and business is based on works related to Indonesia, Malaysia and Thailand.Results. It has been established that in “developmental states” the relations between the state and business are built into the political structure of society, in which centralized governance allows states to ensure political stability, reduce transaction costs for private entities, motivate entrepreneurship and create additional opportunities for economic development, and as a result - increasing the welfare of society.Conclusions. The example of the countries of East and Southeast Asia shows that the success of a “developmental state” is possible only when the political settlement enables the ruling elites to have the law enforcement capabilities to conduct an effective, nationally-oriented industrial policy necessary for the further improvement of the country’s technological capabilities. The rapid economic development of “developmental states”, which has led to talk of a “miracle”, raises the question of the possibility of using this experience in other regions of the world, including the EAEU countries.